A systematic review on whistleblowing intention studies in Malaysia / Sakka Nordin ... [et al.] - Nordin, Sakka; Ambad, Sylvia @ Nabila Azwa; Andrew, Jasmine Vivienne; Abdullah, Sylvia @ Syahidah; Esther, Karen (Universiti Teknologi MARA, Perlis, 2021)
Corruption in Malaysia public sector diminishes public trust in the government and other key institutions' ability in practising integrity and transparency in managing resources, including the national assets and public money. Past researches have given an inadequate understanding of whistleblowing intention factors in Malaysia. Thus, this study's primary goal is to conduct a systematic review of the studies on factors influencing whistleblowing intention among public officials that involve the Theory of Planned Behaviour (TPB) as a baseline model. This paper presents a discussion on the existing studies that focus on whistleblowing intention in Malaysia guided by the PRISMA Statement (Preferred Reporting Items for Systematic reviews and Meta-Analyses) review method. The article search on the Scopus, Web of Science and Google Scholars databases have identified nineteen whistleblowing intention related studies. However, only eleven studies throughout 2010-2019 met the criteria set for this study. TPB can be extended for future studies on whistleblowing intention in Malaysia. Other factors that are not found in the articles serve as a gap for future studies. The outcome of this article is to provide direction for future studies focusing on theoretical and practical implications for policymakers, government organisations and agencies and facilitating public officials in handling whistleblowing matter. Besides, it also provides support to whistleblowers in reporting corruption to improve accountability and integrity among public officials, especially in Sabah.